2023
DOI: 10.33448/rsd-v12i1.39270
|View full text |Cite
|
Sign up to set email alerts
|

Uso de aplicativos para contagem de carboidratos como ferramenta de auxílio no autogerenciamento do diabetes mellitus tipo 1: uma revisão sistemática

Abstract: Aplicativos para a contagem de carboidratos (CCHO) contribuem com inúmeras possibilidades no apoio ao tratamento de pessoas com diabetes, auxiliando na terapia nutricional. Contudo, existe uma quantidade escassa de estudos que avaliam o uso dessa tecnologia, tornando de grande valia identificar seus possíveis benefícios. O presente estudo teve como objetivo verificar o uso de aplicativos para CCHO no autogerenciamento do tratamento do diabetes mellitus tipo 1 (DM1). Trata-se de uma revisão sistemática, realiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…As for the use of apps and the food scale, using specific and nonspecific CC apps and using the food scale to do the CC, when eating something different than usual and to make culinary recipes was associated with having adequate HbA1c in this study. Using mobile apps and food scales helps to perform CC more accurately and frequently, optimizing glycemic control and reducing counting errors (49)(50)(51). In the study by Trawley et al (52), the use of apps among people with T1DM to perform CC was associated with a lower self-reported HbA1c value and a higher frequency of glucose monitoring, corroborating the result found in the present study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As for the use of apps and the food scale, using specific and nonspecific CC apps and using the food scale to do the CC, when eating something different than usual and to make culinary recipes was associated with having adequate HbA1c in this study. Using mobile apps and food scales helps to perform CC more accurately and frequently, optimizing glycemic control and reducing counting errors (49)(50)(51). In the study by Trawley et al (52), the use of apps among people with T1DM to perform CC was associated with a lower self-reported HbA1c value and a higher frequency of glucose monitoring, corroborating the result found in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…In the systematic review by Dantas et al. ( 50 ) it was concluded that the use of CC applications contributes to better glycemic control in patients with T1DM, which is confirmed with the reduction of HbA1c.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A study with Iranian adolescents showed a diet rich in fat and sodium pattern, mainly in obese boys, with lower consumption of trans fatty acids, saturated fatty acids, and sodium being recommended (ROUHANI et al, 2023). A systematic review explored applications for counting carbohydrates, what corroborated an improvement in the glycemic profile (DANTAS et al, 2023). These facts can be used in complementary nutritional consultation.…”
Section: Discussionmentioning
confidence: 99%
“…The 2019 Coronavirus (COVID- 19) pandemic has infected million of people worldwide and affected the entire population, including children (ages [5][6][7][8][9][10][11][12] and adolescents (ages [13][14][15][16][17] who, in late April 2020, made the transition to remote learning after school closures. This fact, added to socio-behavioral adaptations, such as social distancing and quarantine, has impacted this population's daily activities and lifestyle (BATES et al, 2020; IRWIN et al, 2022).…”
Section: Introductionmentioning
confidence: 99%